(untitled) (NOURA: Jurnal Kajian Gender dan Anak, 2019)
Corruption is a crucial problem for the the Indonesian nation. Therefore, concrete action is needed to eradicate corruption. Real efforts that can be made in the family environment by teaching the values ​​of anti-corruption integrity to children because the family is the first and foremost madrasa in teaching good values. There are ten anti-corruption integrity values ​​that parents have to teach to children including honest, caring, independent, disciplined, responsible, hard work, simple, courageous, fair and patient. The implementation of these values ​​can be carried out by parenting, done consistently and continuously, commitment to always support the child in the process, and religiosity in the family